Agricultural mechanization and reduced tillage: antagonism or synergy? - Moti Jaleta; Frédéric Baudron; Branka Krivokapic-Skoko; Olaf Erenstein (International Journal of Agricultural Sustainability, 2019)
This paper reviews agricultural mechanization and reduced tillage use in the context of sustainable intensification in developing country agriculture. The scoping review includes selected and contrasting cases – including Zimbabwe (manual systems), Bangladesh (2-wheel – single axle tractor systems), India (4-wheel – i.e. 2 axles tractor systems), Kazakhstan (mechanized systems) and Brazil (diverse systems). The expansion of reduced tillage appears strongly associated with the level of agricultural mechanization – facilitated by a number of common drivers and contextualized by the prevailing farm power and intensity of tillage. Soil conservation, timely planting and farm power savings in crop establishment are important drivers for the expansion of reduced tillage across the world, facilitated by conducive markets, institutional and policy environments and the integration of diverse actors to introduce, adapt and promote the necessary components.